A Test on a Production Network-Based RBC Model - Witkowski , Dariusz (Studia Oeconomica Posnaniensia, 2018)
What is the origin of aggregate fluctuations represents one of the important questions in macroeconomics and constitutes a challenge to macroeconomic modelling. Battiston, Delli Gatti, Gallegati, Greenwald, & Stiglitz (2007) present an intuitive model which, relying on firms’ bankruptcy and rebirth as a source of business cycle dynamics, is able to replicate stylized facts of industrial demography. Although firms’ exit behaviour constitutes the core of their framework, the empirical investigation in terms of ability to match the business exit patterns observed in the data is still unexplored. This study contributes to the existing literature by examining if the firms’ exit patterns observed in the model of Battiston et al. (2007) can replicate those observed in U.S. business statistics. The results show that the model is able to partially match firms’ exit patterns in the data, specifically the counter-cyclicality of exit rate and the co-movement between the aggregate output growth and the average size of exiting firms. On the other hand, the results of a calibrated model are counterfactual in terms of a strong negative contemporaneous correlation between the average size of exiting firms and output growth.